Deposition and transport of Pseudomonas aeruginosa in porous media: lab-scale experiments and model analysis - Kwon, Kyu-Sang; Kim, Song-Bae; Choi, Nag-Choul; Kim, Dong-Ju; Lee, Soonjae; Lee, Sang-Hyup; Choi, Jae-Woo (TAYLOR & FRANCIS LTD, 2013)
In this study, the deposition and transport of Pseudomonas aeruginosa on sandy porous materials have been investigated under static and dynamic flow conditions. For the static experiments, both equilibrium and kinetic batch tests were performed at a 1:3 and 3:1 soil:solution ratio. The batch data were analysed to quantify the deposition parameters under static conditions. Column tests were performed for dynamic flow experiments with KCl solution and bacteria suspended in (1) deionized water, (2) mineral salt medium (MSM) and (3) surfactant+MSM. The equilibrium distribution coefficient (K-d) was larger at a 1:3 (2.43mLg(-1)) than that at a 3:1 (0.28mLg(-1)) soil:solution ratio. Kinetic batch experiments showed that the reversible deposition rate coefficient (k(att)) and the release rate coefficient (k(det)) at a soil:solution ratio of 3:1 were larger than those at a 1:3 ratio. Column experiments showed that an increase in ionic strength resulted in a decrease in peak concentration of bacteria, mass recovery and tailing of the bacterial breakthrough curve (BTC) and that the presence of surfactant enhanced the movement of bacteria through quartz sand, giving increased mass recovery and tailing. Deposition parameters under dynamic condition were determined by fitting BTCs to four different transport models, (1) kinetic reversible, (2) two-site, (3) kinetic irreversible and (4) kinetic reversible and irreversible models. Among these models, Model 4 was more suitable than the others since it includes the irreversible sorption term directly related to the mass loss of bacteria observed in the column experiment. Applicability of the parameters obtained from the batch experiments to simulate the column breakthrough data is evaluated.